Permaculture Planning and Japanese Culture of Western São Paulo: The Experience of the Cultural Agricultural Sports Association of Presidente Prudente (ACAE) - Inague, Patrícia; Paiva, Letícia Aparecida de; Okimoto, Fernando Sérgio (Technical and Scientific Journal Green Cities, 2025)
This article explores permacultural planning as an alternative tool for the restoration, preservation, and dissemination of Japanese culture, focusing on the development of a master plan for the Japanese entity ACAE. The study uses the methodology proposed by Ferreira, Okimoto, and Paiva (2024) to elaborate a comprehensive plan that integrates ACAE's three fundamental pillars: culture, agriculture, and sports. Through the application of this methodology, it was possible to develop a master plan that meets the needs of the various users of the club, creating uses and environments that promote ecological restoration, the preservation of cultural traditions, and the dissemination of Nippon culture. The proposed permacultural planning not only values the traditional and contemporary aspects of Japanese culture but also offers a sustainable model that can be replicated in other communities. The results demonstrate that integrating permacultural practices into the planning of cultural spaces can offer significant benefits, both for the local community and for the preservation of cultural heritage. This study contributes to the field of culture-applied permaculture and highlights the importance of integrated approaches for the sustainable development of community spaces.
Keywords: Japanese culture; Permacultural planning; Cultural preservation